Hardiness and quality of life in NAFLD patients: pilot study - Skurat, Катерина (Psychosomatic Medicine and General Practice, 2021)
Background. The prevalence of NAFLD in the general population is approximately 20-30% in Western countries and 5-18% in Asia. NAFLD consists of a range of liver diseases, ranging from simple deposition of fat in the liver (steatosis; called nonalcoholic fatty liver or NAFLD) to steatosis with associated hepatocyte lesions (NASH). Importantly, NASH, in turn, can lead to fibrosis, cirrhosis, and, in some cases, hepatocellular carcinoma (HCC). The aim of the study. The purpose of the study: to increase the effectiveness of treatment of patients with non-alcoholic fatty liver disease by optimizing lifestyle with psycho-corrective effects. Research methods. The study is conducted based on the gastroenterology department of the Center for Innovative Medical Technologies of the National Academy of Sciences of Ukraine. As of September 2021, a total of 23 patients with the non-alcoholic fatty liver disease aged 37 to 58 years (mean age 46.5 years) were examined, including 11 men (47.8%) and 12 women (52.2%). The initial survey and testing of patients are carried out on days 1-3 of admission to the hospital. The following methods were used in the study: "10 words" by AR Luria, Schulte tables, SRRS (Holmes and Ray scale), S. Muddy's vitality questionnaire, modified by D.A. Leontieva, SF-36 (Medical Outcomes Study Short Form). Results. In all interviewed patients, the level of cognitive functioning was at a satisfactory level. The level of both the actual viability and its subscale in most respondents was within the average. All respondents, without exception, had a moderate risk of developing the disease due to life events, which is of some concern. However, further research is likely to provide more information and an opportunity to confirm or refute the hypothesis formed at this stage of the study. According to the results of the assessment of the quality of life of patients, slightly less than half of the respondents (47.8%) have a reduced level of quality of life. Conclusions. The results presented in the article are another confirmation of the relevance and necessity of research aimed at identifying influencing factors and means to improve quality of life and the formation of a healthy internal picture of the disease of patients with non-alcoholic fatty liver disease.